Backfilling performance of mixtures of dredged river sediment and iron tailing slag stabilized by calcium carbide slag in mine goaf. (20th November 2018) - Chu, Chengfu; Deng, Yongfeng; Zhou, Annan; Feng, Qi; Ye, Hao; Zha, Fusheng
Highlights: Recycling of wastes as backfilling materials in mine goaf is an optional way. CCS replacement of cement can elevate the slump value of DRS and ITS mixture. Optimal proportion among DRS, ITS, OPC and CCS is 60:40:16:4 in mass in this case. An updated expression to predict the strength is proposed just with two variables. Abstract: Re-utilization of industrial wastes or by-products in construction, including dredged river sediments (DRS), iron tailing slag (ITS) and calcium carbide slag (CCS) etc., can reduce the construction cost, decrease the storage requirement and also be of great benefit to the environment. In this research, the aforementioned wastes ( i.e., DRS, ITS and CCS) were synthetically recycled and used as the backfilling materials in the mine goaf to solve the problem of subsidence. Systematic laboratory experiments were conducted to ensure that these recycled materials can fulfill the requirement on the slump value and unconfined compressive strength after 7-day's curing. The results show that despite that Ordinary Portland cement (OPC) suppresses the slump value, CCS elevates the flowability, and then the maximal flowability is achieved when the mass ratio of DRS to ITS was 70:30 with a cement content of 16.7%. ITS addition into DRS upgrades the strength of the mixtures of DRS and ITS stabilized by OPC and CCS for the skeleton effect and water content reduction. The optimal proportion between DRS, ITS, OPC and CCS in this case is 60:40:16:4 in mass, with a slump value of about 160, and unconfined compression strength after 7-day's curing about 2.8 MPa. At last, a simple expression to predict the strength of the backfilling materials was proposed referring the gel-space theory and the concept of volumetric solid content, where just two variables ( i.e., the binder content and the volumetric solid content) can characterize this complex matrix.